PREDICTION OF A COURSE OF CHRONIC SUPPURATIVE OTITIS MEDIA BY THE ANALYSIS OF COMBINATIONS OF GENE POLYMORPHISMS OF PROINFLAMMATORY AND ANTI-INFLAMMATORY CYTOKINES - E. V. Bayke (Acta Biomedica Scientifica, 2017)
The urgency of otogenic intracranial complications in modern otolaryngology is connected with difficulties of the early diagnostics, severe course of the disease and rather high percentage of fatalities. All of that defines practical value of the matters aimed to improve definition of an individual's liability to aggressive course of chronic suppurative otitis media, which can cause direct threat for a patient's life. The aim of the study was to increase accuracy of diagnostics of destructive course of chronic suppurative otitis media with forecasting of intracranial pathology at early stages of inflammation. Molecular genetic analysis was conducted of human DNA from 300 patients with chronic purulent otitis media and 100 healthy individuals for the presence of genotype variants of genes cytokines: IL-1b (511Т/С, 31 Т/C), IL-10 (1082 G/A, 819 С/Т). The SNP (single nucleotide polymorphism) distribution of gene cytokines in the studied groups corresponded Hardy-Weinberg equilibrium (HWE > 0.05). We found that a combination of genes IL-1b 511Т/С, IL-10 1082A/A, IL-10 819С/С, IL-1b 31C/C occurred correspondingly in 57.8,13.6 and 22 % of patients with attic disease, and were associated with expressed caries-destructive course of chronic suppurative otitis media complicated by intracranial pathology. The combination of gene polymorphisms of IL-1b 511 Т/Т, IL-10 1082 G/A, IL-10 819 С/T, IL-1b 31 T/C in 46 % of patients was clinically manifested by mucosal process in the middle ear.